IMPLEMENTASI PRINSIP GOOD AMIL GOVERNANCE DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA PAYAKUMBUH - Nasrizal -; Sinta Westika Putri; Eva Suryany; F. Yasmeardi; Maiyulnita - (Jurnal Public Administration, Business and Rural Develoment Planning, 2022)
The application of the principles of Good Amil Governance (GAG) is expected to reduce the problems faced by Badan Amil Zakat (BAZ), increase public trust, raise Zakat, Infak and Sadaqah (ZIS) funds more optimally, and target distribution is more precise and meaning for those who deserve it. This study aims to describe and analyze the implementation of the principles of Good Amil Governance in BAZNAS Payakumbuh. Using a qualitative descriptive research method by collecting data and information from interviews and documentation, which is then analyzed using interactive methods. The results of the study show that overall all the instruments from the principles of Good Amil Governance (GAG) have been applied in a good category at BAZNAS Payakumbuh. However, in the implementation of each instrument of the Principles of Good Amil Governance (GAG) there are still complex obstacles that must be faced by BAZNAS Payakumbuh City.